PERENCANAAN MASTER PLAN TERPADU PONDOK PESANTREN DARUL KHAIR SEBAGAI UPAYA PENGEMBANGAN KAWASAN PENDIDIKAN ISLAM - Hendri Silva; Boby Samra (Komunitas Manajemen Kompetitif, 2026)
This community service program was implemented through mentoring for the master plan of the Darul Khair Islamic Boarding School in Pekanbaru, Tenayan Raya, located on Jalan Badak Ujung, Bencag Lesung, Tenayan Raya District, Pekanbaru City. This mentoring program is expected to ensure the optimal development and organization of the Islamic boarding school environment. Through this program, it is hoped that the management of the Darul Khair Islamic Boarding School in Pekanbaru will be assisted in improving the school's environment. The community service program targeted the Darul Khair Islamic Boarding School in Pekanbaru, Tenayan Raya. The program involved a field survey to assess the condition of the school, followed by the design of the master plan and discussions with partners to finalize the design. The training program demonstrated that the Darul Khair Islamic Boarding School has been instrumental in improving the school's environment. Keywords: Master plan, Development, Environment